Student-Parent-Teacher (SPT-CARE): online school management system. - Kartiwi, Mira; Othman, Abdul Rauf; Tuan Aziz, Tuan Noor Azinie (IIUM Press, 2011)
This study aims to examine the potential use of a school management system that would enable a three-way communication, which is the communication between students, parents and teachers. A pilot study was conducted to allow the researcher to identify the scope and problems needed to be addressed by the system. This pilot study involved a survey of a number of students, parents and teacher of an Islamic school in Kuala Lumpur area. The result of the pilot study was translated into requirements of which a prototype is then built as one of deliverables of this study.